A reconstrução da etnicidade na arena turística: o caso do roteiro de turismo rural cultural Caminhos de Pedra - Bento Gonçalves - RS - Michelin, Rita Lourdes (My University, 2014)
The present research is about the reconstruction of the Italian ethnicity in the tourist arena of Distrito de Sao Pedro community, rural area of Bento Gonçalves - RS. It intends to demonstrate the ethnicity reconstruction process through the influences this can suffer by tourism. Thereby this research intends to analyse questions as internal and external influences that the culture of a specific group can suffer, demonstrating how dynamic the cultural traces can be. Besides that, this dissertation presents the relation between hosts and guests as a way to show in which way tourism can use a society culture as an attractive issue and how this can collaborate to the ethnicity reconstruction of a community. For that it uses the methodology of ethnography with participative observation, photographic register and photo-ethnographic narrative, aiming the ethnicity perception of this tourist arena, by the point of view of the community people themselves on their routine and their relation with the tourists.
A presente pesquisa versa sobre a reconstrução da etnicidade italiana na arena turística da comunidade do Distrito de São Pedro, zona rural do município de Bento Gonçalves - RS, buscando demonstrar o processo de reconstrução da etnicidade através das influências que essa pode receber do turismo. Sendo assim, busca-se analisar como influências internas e externas que a cultura de um determinado grupo pode sofrer, demonstrando a dinamicidade dos traços culturais. Além disso, trata-se da relação entre visitantes e visitados, buscando demonstrar de que maneira o turismo pode utilizar a cultura de uma sociedade como atrativo e se colabora na reconstrução da etnicidade de uma comunidade. Para tanto, utilizou-se a metodologia da etnografia com observação participante, registro fotográfico e narrativa fotoetnográfica, tendo por objetivo perceber a etnicidade da comunidade da arena turística a partir da visão dos próprios moradores no seu cotidiano e nas suas relações com os turistas.
Keywords: Turismo; Turismo; Cultura; Etnicidade; Italianidade; Caminhos de Pedra - Bento Gonçalves (RS); Distrito de São Pedro - Bento Gonçalves (RS); Rio Grande do Sul; Colonização - Italiana, Região (RS); Tourism; Culture; Ethnicity; Italianity; Caminhos de Pedra - Bento Gonçalves (Brazil); Distrito de São Pedro - Bento Gonçalves (Brazil); Rio Grande do Sul (Brazil); Italian colonization